Influence of multilayer cloud characteristics on cloud retrieval and estimation of surface downward shortwave radiation - Ri, Ana; Ma, Run; Shang, Huazhe; Xu, Jian; Tana, Gegen; Shi, Chong; He, Jie; Bao, Yuhai; Chen, Liangfu; Letu, Husi (Frontiers in Environmental Science, 2022)
There are significant uncertainties in the retrieval accuracy of multi-layer clouds with different phases, leading to derivation in the subsequent estimation of the surface downward shortwave radiation (DSR). Single-layer clouds are generally assumed for the retrieval of cloud optical and microphysical properties from satellite measurements, although multi-layer clouds occur often in reality. In this paper, the impact of multilayer clouds (thin ice clouds overlying lower-level water clouds) on the retrieval of cloud microphysical properties is simulated with the radiative transfer model RSTAR. The stimulated results demonstrate the impact of double-layer clouds on the accuracy of retrieval of cloud parameters and estimation of DSR. To understand the uncertainties of the input parameters, thorough sensitivity tests are simulated by the RSTAR in result part. Compared with the retrieval results of single-layer clouds, when the ice particle model of upper-layer cloud is assumed to be ellipsoidal, the COT for ice cloud is 1.2 and the COT for water cloud is 32.45, the relative derivation is 0.63%. When the upper-layer ice cloud is assumed to be hexagonal column, the relative derivation is 55.34% .The COT for ice cloud is 2, and the COT for water cloud is 58.4. In addition, relative derivation exhibited an increasing trend as reflectance increased. This finding can provide a basis of reference for the estimation accuracy of radiative forcing in the IPCC report and the subsequent enhancement and improvement of retrieval algorithms.